Analysis of exogenous intoxications in the State of Piauí from 2013 to 2017 (Research, Society and Development, 2021)
Introduction: Intoxication is characterized as the manifestation of signs and symptoms, due to the harmful effects caused in a living organism, as a result of its interaction with a certain exogenous chemical substance. According to the World Health Organization (WHO), annually 1.5 to 3% of the population are intoxicated on the national scene, corresponding to approximately 4,800,000 new cases each year, with a total of 0.1 to 0.4 % of intoxications lead to death. These problems affected in accidental or intentional ways are considered to be important causes of health problems. Objective: Describe and analyze exogenous intoxication data recorded in the Notifiable Diseases Information System (SINAN), in the state of Piauí, between 2013 and 2017. Methodology: This is an ecological, descriptive study, with a quantitative approach to cases of poisoning by exogenous agents reported in the state of Piauí, in the period from 2013 to 2017. Data were obtained through SINAN. The following variables were researched: municipality of notification, age group, evolution, circumstances, type of exposure and confirmation criteria. The data were analyzed using absolute and percentage frequencies and organized in tables and graphs using Microsoft Office Word, 2016; Microsoft Office Excel, 2016 and TabWin version 4.14. Results: 5,836 confirmed cases of exogenous poisoning were reported in individuals living in Piauí, concentrated in Picos and in the capital Teresina, with 16.48% and 32.74% of the records, respectively. There was unanimity regarding the most affected age group, 20-39 years. The main circumstance of intoxications was the attempted suicide (44.47%), with acute single exposure to drugs being the predominant medium, with 1,880 cases. Of the total occurrences, 75.88% had a cure without sequelae, 0.94% resulted in a cure with sequelae, 1.09% died and 21.31% of the cases were ignored. The clinical criterion was the main means of confirmatory diagnosis, corresponding to 53.75% of the total of notifications, followed by the clinical-epidemiological criterion with 30.58%. Conclusion: Intoxication is a recurrent event in the state of Piauí, associated, in most cases, with medications and suicide attempts, justifying the need to carry out educational actions with the population and permanent education with health professionals. It is also emphasized the importance of reporting cases of exogenous intoxication for investigation of outbreaks, adequate care for patients and the development of prophylactic measures.